Advances in Electronics, Communication and Computing ETAEERE-2016 - Kalam, Akhtar; Das, Swagatam; Sharma, Kalpana; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book is a compilation of research work in the interdisciplinary areas of electronics, communication, and computing. This book is specifically targeted at students, research scholars and academicians. The book covers the different approaches and techniques for specific applications, such as  particle-swarm optimization, Otsu's function and harmony search optimization algorithm,  triple gate silicon on insulator (SOI)MOSFET, micro-Raman and Fourier Transform Infrared Spectroscopy (FTIR) analysis, high-k dielectric gate oxide, spectrum sensing in cognitive radio, microstrip antenna, Ground-penetrating radar (GPR) with conducting surfaces, and digital image forgery detection. The contents of the book will be useful to academic and professional researchers alike. .
Analysis of Authentication and Key Agreement (AKA) Protocols in Long Term Evolution (LTE) Access Network -- Impact of M2M Traffic in Random Access Channel over LTE Networks -- Predictive Modeling of Students Performance through the Enhanced Decision Tree -- A new pulse width modulation technique with hybrid carrier arrangement for multilevel inverter topology -- Watershed-Matching Algorithm: A New Pathway for Brain Tumor Segmentation -- A Compact Slotted Textile Patch Antenna for Ultra Wide Band Application -- Triple Gate SOI MOSFET -- Wearable Antennas for Medical Application: a Review -- Characterization of Silicon carbo-nitride Thin Films -- Packet Sniffing and Network traffic analysis using TCP -A New Approach -- Investigation of structural and electronic environments of nitrogen doped CVD grown DLC films -- Improving Convergence in iBGP Route Reflectors -- Design of Circularly Polarized Antenna with different  Iteration for UWB applications -- Weighted Wavelet Tree Sparsity Regularization for Compressed Sensing Magnetic Resonance Image Reconstruction -- An approach for Visual Cryptography Scheme on Color Images -- X-Band Patch Array Antenna -- A Compact Pentagonal Textile Microstrip Antenna for Wide Band Application -- Similarity Measurement of Gene Using Arc Tan Function in Gene Ontology.
Keywords: Electronic circuits; Telecommunication; Artificial intelligence; Electronic Circuits and Systems; Communications Engineering, Networks; Artificial Intelligence